IMPACT OF INTENSITY MODULATED RADIATION THERAPY ON THE SALIVARY GLANDS FUNCTION AND SALIVA FLOW RATE - Gjurovski, Sonja Rogoleva; Popovski, Vladimir; Kostadinova, Lenche; Nikolovski, Bruno (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
In patients with head and neck cancer, the most common issue after radiation treatment is xerostomia and the consequences of that, which are affecting the quality of everyday life of the patient. Subjectively xerostomia is manifested as dryness in the oral cavity, followed with obstructed chewing and swallowing of the food. Mostly it happens because of the death of the cells in the gland that are supposed to be dividing, caused by the radiation. To improve patientsâ€™ life after treatment, IMRT approach has been considered to be a better solution for the gland tissue sparing during the radiation treatment, therefore, to decrease the severity and the intensity of the following  xerostomia. The IMRT technique allows the chosen dose of radiation to be applied specifically on the tissue where it is supposed to be, sparing the surrounding healthy parts from the unnecessary radiation. The aim of this study was to evaluate the influence of the Intensity Modulated Radiation therapy (IMRT), with different intensity and dosage, on the function of salivary glands. For this study were analyzed total number of 87 surveys, 41 of them were used for detail analysis. This study is based on narrative review on published articles written in English language, reporting results related to the use of Intensity modulated radiation therapy treatment in patients with head and neck cancer. The gathered results have shown that the function of the salivary glands after radiation treatment can be in many cases protected during the treatment, or even restored to some level, therefore the resulting xerostomia can be reduced and itsâ€™ following negative effects affecting the patientsâ€™ life could be minimized by using the improved technique IMRT. In many studies the evaluated levels of xerostomia have been found to be significantly lower in the groups of patients treated with IMRT technique, compared with the other group of patients treated with conventional radiation therapy. Also, a big influence has the dosage of the radiation beams, on what depends on the outcome of the salivation function in patients treated with radiation therapy. Key words: Intensity modulated radiation therapy, xerostomia, salivary glands hypo-function, saliva reduction, saliva flow rate, salivary gland sparing. https://doi.org/10.55302/JMS2251172rgj